2005
DOI: 10.1007/s00251-005-0061-6
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic significance of HLA class I genes in measles virus-specific IFN-γ and IL-4 cytokine immune responses

Abstract: The variability of immune responses modulated by human leukocyte antigen (HLA) genes and secreted cytokines is a significant factor in the development of a protective effect of measles vaccine. We studied the association between type 1 helper T cells (Th1)- and Th2-like cytokine immune responses and HLA class I alleles among 339 schoolchildren who previously received two doses of the measles vaccine. Median values for measles-specific interferon gamma (IFN-gamma) and interleukin-4 (IL-4) cytokines were 40.7 pg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 44 publications
1
42
0
1
Order By: Relevance
“…Prior population-based studies found associations with both class I and class II alleles and measles vaccine immune response [22][23][24]. Subsequent studies suggest the significance of HLA genes in measles virus-specific IFN-γ and IL-4 cytokine immune responses [25,26]. The class I HLA-A (*0101 and *3101) and HLA-Cw (*0303 and *0501) alleles have been significantly associated with measles virus-induced IFN-γ secretion [25].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Prior population-based studies found associations with both class I and class II alleles and measles vaccine immune response [22][23][24]. Subsequent studies suggest the significance of HLA genes in measles virus-specific IFN-γ and IL-4 cytokine immune responses [25,26]. The class I HLA-A (*0101 and *3101) and HLA-Cw (*0303 and *0501) alleles have been significantly associated with measles virus-induced IFN-γ secretion [25].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies suggest the significance of HLA genes in measles virus-specific IFN-γ and IL-4 cytokine immune responses [25,26]. The class I HLA-A (*0101 and *3101) and HLA-Cw (*0303 and *0501) alleles have been significantly associated with measles virus-induced IFN-γ secretion [25]. Likewise, class II HLA-DRB1 (*0301, *0901 and *1501) and DRB1 (*0103, *0701 and *1101) alleles were associated with IFN-γ and IL-4 secretion, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations